Pengaruh Profitabilitas, Umur Perusahaan, Dan Struktur Modal Terhadap Audit Delay Dengan Ukuran Perusahaan Sebagai Variabel Moderasi (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2019-2023) - Mayesa Sintiya; Ruswan Nurmadi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of profitability, firm age, and capital structure on audit delay, with firm size as a moderating variable, in manufacturing companies listed on the Indonesia Stock Exchange for the 2019–2023. The sample was obtained through purposive sampling, with companies meeting the research criteria. The population in this study was 282 manufacturing companies listed on the Indonesia Stock Exchange. In comparison, the sample in this study amounted to 40 companies over the 5 years of research, so the total sample in this study wa 200 samples. This study is an associative study with a quantitative approach. The data used are secondary from the companies' annual financial reports. The data analysis techniques used were multiple linear regression and Moderated Regression Analysis (MRA). The study's results indicate that profitability and firm age have a negative effect on audit delay, while capital structure does not significantly impact audit delay. The results of the MRA test indicate that firm size moderates the impact of profitability and firm age on audit delay. In contrast, firm size does not moderate the effect of capital structure on audit delay.